2016
DOI: 10.4238/gmr.15038387
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Toona sinensis Roem in China revealed by ISSR and SRAP markers

Abstract: ABSTRACT. Toona sinensis Roem has an important value as a type of traditional vegetable and Chinese medicinal herb, and is also a valuable source of wood in China. In this study, we used the inter-simple sequence repeat (ISSR) and sequence-related amplified polymorphism (SRAP) markers to assess the level and pattern of genetic diversity in five domesticated T. sinensis populations in China. Our results indicated a relatively low level of genetic diversity both at species (Hs = 0.1662, 0.2098, respectively) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…It is a powerful tool for estimating the characteristics of genetic diversity and distinguishing among individuals from different sources (EL-Bakatoushi & Ahmed, 2018; Nair et al, 2018; Kumar & Agrawal, 2017; Zheng et al, 2012). Sequence-related amplified polymorphism (SRAP) and inter-simple sequence repeats (ISSRs) markers are dominant markers based on PCR and have been widely used in different genetic diversity studies (Xing et al, 2016; Gaafara et al, 2017; Sun et al, 2018; Khalifa et al, 2016). Sequence-related amplified polymorphism is a PCR-based molecular marker developed by Li & Quiros (2001), which uses a unique dual primer design to amplify specific regions of open reading frames (ORFs).…”
Section: Introductionmentioning
confidence: 99%
“…It is a powerful tool for estimating the characteristics of genetic diversity and distinguishing among individuals from different sources (EL-Bakatoushi & Ahmed, 2018; Nair et al, 2018; Kumar & Agrawal, 2017; Zheng et al, 2012). Sequence-related amplified polymorphism (SRAP) and inter-simple sequence repeats (ISSRs) markers are dominant markers based on PCR and have been widely used in different genetic diversity studies (Xing et al, 2016; Gaafara et al, 2017; Sun et al, 2018; Khalifa et al, 2016). Sequence-related amplified polymorphism is a PCR-based molecular marker developed by Li & Quiros (2001), which uses a unique dual primer design to amplify specific regions of open reading frames (ORFs).…”
Section: Introductionmentioning
confidence: 99%
“…Brito et al (2016) analyzed the genetic diversity of Varronia curassavica accessions and observed that 14 primers resulted in a mean amplification of 11 fragments. Xing et al (2016) observed the mean value of 6.9 fragments from 15 primers in a study with Toona sinensis Roem.…”
Section: Discussionmentioning
confidence: 99%
“…and T. sureni Merr. The two species have a difference in morphology and genetic characteristics (Li et al 2015;Xing et al 2016;Jayusman et al 2017;Lin et al 2018). However, the differences in their basic wood properties, especially their anatomical properties, have not been clarified.…”
Section: Introductionmentioning
confidence: 99%